MENTAL ACTIVITIES AND LINGUISTIC STRUCTURES - Bernard Pottier (Al-Lisaniyyat)
Between the world - real or imaginary - and the linguistic domain, there is an area which is not directly observable ; this is the area of conceptualization. For many years linguists have been devoting their attention to this field of investigation. Eighty years ago, Gustave Guillaume set about establishing schematic repre-sentation of mental trajectories (the radical binary tensor). This line of research has been pursued, first by European semanticians, then by American cognitivists, oscillating between topo-synthetic gra-phic representation (the geometric approach) and logico-analytical formulation (the algebraic approach). The hypothesis is that the speaker’s conceptualization of the universe is based on a reduced number of simple mental mechanisms and that these underlie all the more complex operations.